What Constitutes Effective Interprofessional Education Amongst Health Related Disciplines : A Literature Review - Elly Wardani; R. Rachmah; Putri Mayasari; Mayanti Mahdarsari (The Faculty of Veterinary Medicine of Syiah Kuala University, 2019)
Interprofessional Education (IPE) is considered an educational strategy that has potential benefit for improving teamwork and collaboration in practice, leading to improved patient outcomes. As the development and implementation of curricula that integrate IPE requires significant resources, its adoption should be based on evidence of effectiveness. The purpose of this literature review is to identify what constitutes effective interprofessional education amongst health related disciplines. A literature search was conducted using Science Direct, BMC, Elsevier and Joint Commission Journal for the years 2009-2018. A total of 15 studies met the established inclusion criteria. The use of IPE among health related disciplines is one effective way to solve several problems, and its particularly improves patient safety. What constitutes effective interprofessional education amongst health related disciplines are possibly viewed from some aspects, such as efficiency, effectiveness, learning strategy, power, patient and learner safety and readiness to practice, interprofessional curriculum, roles and relationships, and learning outcomes.